Bio-insecticide’s Extract of Scented Root (Polygala paniculata) in Controlling the Mosquito Aedes aegypti (L.) - Wahyuni, Denai; Sari, Nila Puspita; Jasril, Jasril; Syahri, Jufrizal (UI Scholars Hub, 2022)
Controlling Aedes aegypti mosquitoes with chemical insecticides causes resistance on humans, environmental residues, and contaminates food and water. Polygala paniculata is a potential alternative to insecticides in controlling Ae. aegypti. This study aimed to determine the effect of the Insecticide Score of P. paniculata extracts on the mortality of Ae. aegypti mosquitoes based on KT50. A total of 20 mosquitoes for each concentration were used to examine the effectiveness of 10%, 15%, 20%, and 25% concentration of P. paniculata extracts compared to a positive and a negative control with four replications. The results showed that P. paniculata extracts had an effect on Aeaegypti mosquito mortality. There were significant differences in mortality rate between concentrations (Kruskal-Wallis test, p = 0.001). Spearman Correlation test gave a p-value of 0.008 < 0.05. Similarly, there was a weak but significant correlation between plant extract concentration and mortality (Spearman correlation: r = +0.312, p = 0.008). The 10% and 15% concentrations had KT50with Insecticide Scores of 1 and 2, respectively, implying that both had no knockdown effect. A 20% concentration had a KT50 with an Insecticide Score of 3, indicating a weak knockdown effect, whereas a 25% concentration had KT50with an Insecticide Score of 5, signifying a quick knockdown effect. These results show that a 25% concentration has a quick knockdown time on Ae. aegypti mosquitoes. Therefore, extract P. paniculata extract at a concentration of 25% has a potential for use as a bio-insecticide in controlling Ae. aegypti mosquitoes.